Persepsi Guru PJOK dan Guru Kelas Terhadap Ketersediaan Fasilitas Pendidikan untuk Pembelajaran Aktif di SD Negeri 1 Gobras - Afifah Avilani; Sri Purnama Sari; Devi Sri Agustin; Erni Pitriani; Desi Nadia Ulpah; Dinda Nurfarida; Chandra Rizky Noviandi; Rahmat Permana (Lembaga Pengembangan Kinerja Dosen, 2025)
The availability of educational facilities is one of the most important factors in enhancing active learning, particularly in the context of Physical Education, Sports, and Health (PJOK) education and classroom settings. Physical education and health is one of the subjects that can help students develop themselves as individuals and social beings so that they grow and develop naturally (Firmasnyah & Rukmana, 2017). The availability of educational facilities is one of the most important factors in enhancing active learning, particularly in the context of Physical Education, Sports, and Health (PJOK) education and classroom settings. The purpose of this study is to understand how PJOK and classroom teachers perceive the availability of educational facilities in schools in promoting active learning. The availability of educational facilities in schools in promoting active learning. The methodology used in this study is a qualitative descriptive technique using interviews to collect data. The research methodology is qualitative descriptive, using data collection techniques through interviews. Qualitative descriptive using data collection techniques through interviews. This study involved physical education teachers and classroom teachers from SDN Dasar 1 Gobras Tasikmalaya. The findings of this study indicate that most teachers believe that educational facilities at schools are adequate but need to be improved to ensure more effective active learning. Additionally, there are differences in perception between physical education teachers and classroom teachers, with physical education teachers emphasizing the importance of facilities for classrooms and sports. Additionally, there are differences in perception between physical education teachers and classroom teachers, with physical education teachers emphasizing the importance of facilities for classrooms and sports.